IMPLEMENTATION OF INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) IN MANAGEMENT ACCOUNTING SYSTEM ON THE QUALITY OF FINANCIAL REPORTS (SLR APPROACH) - Fadhlurrahman, Rafli; Fuadah, Luk Luk (LP2M IBK Nitro, 2025)
This study aims to analyze the impact of implementing International Financial Reporting Standards (IFRS) on accounting management systems and the quality of corporate financial statements. The research method used is a Systematic Literature Review (SLR), with data sources derived from 25 journals indexed in Scopus and SINTA. This study examines changes in accounting policies, the integration of technology into accounting systems, internal control, and challenges in IFRS implementation. The results indicate that IFRS enhances the transparency and comparability of financial statements by reducing earnings management practices and improving the timeliness of loss recognition. Additionally, IFRS encourages companies to adopt more advanced accounting information systems to ensure accuracy and efficiency in financial reporting. However, IFRS implementation also faces challenges, such as the costs of technological adjustments and the need for stronger regulatory oversight. In conclusion, IFRS plays a crucial role in improving financial reporting quality and the effectiveness of accounting management systems, but its success largely depends on a company’s readiness to adapt to regulatory changes. Therefore, it is recommended that companies invest in accounting technology, enhance human resource capacity, and strengthen internal oversight to maximize the benefits of IFRS and mitigate associated risks.